1990
DOI: 10.1002/ajmg.1320370208
|View full text |Cite
|
Sign up to set email alerts
|

Chondrodysplasia punctata, tibia‐metacarpal (MT) type

Abstract: We describe 7 patients with a new form of chondrodysplasia punctata. Its principal clinical manifestations are flat midface and nose, short limbs, and otherwise normal development. Consistent radiologic manifestations in the newborn infant are discrete calcific stippling, coronal clefts of vertebral bodies, short tibiae, and shortness of the 2nd and 3rd metacarpal bones. Radiologic findings in the older child include shortness of tibiae and the 3rd and 4th metacarpals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…This subtype of CDP was first reported as early as 1951 (Haynes and Wangner, 1951), but was described as a discrete entity, TM type by Burck (1982), and hence it is also referred to as CDP, Burck type. It occurs as a sporadic disorder, and both men and women are equally affected suggestive of a probable autosomal dominant mode of inheritance (Rittler et al, 1990). There has been a single report of two affected siblings (Honda et al, 2008) in the literature to date suggesting either a possibility of recessive mode of inheritance or gonadal mosaicism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This subtype of CDP was first reported as early as 1951 (Haynes and Wangner, 1951), but was described as a discrete entity, TM type by Burck (1982), and hence it is also referred to as CDP, Burck type. It occurs as a sporadic disorder, and both men and women are equally affected suggestive of a probable autosomal dominant mode of inheritance (Rittler et al, 1990). There has been a single report of two affected siblings (Honda et al, 2008) in the literature to date suggesting either a possibility of recessive mode of inheritance or gonadal mosaicism.…”
Section: Discussionmentioning
confidence: 99%
“…The initial description of seven cases by Rittler et al (1990), including two cases of Burck (1982) provided the comprehensive clinical and radiographic features of this variety of CDP. These authors also reviewed and included in their description previously reported cases.…”
Section: Discussionmentioning
confidence: 99%
“…The teratogenic effects of alcohol are well documented and there are reports of association between fetal alcohol and CDP (Badois et al, 1983;Maroteaux et al, 1984;Gonzalez Rivera and Ruiz Palomares, 1987;Sadra et al, 1989;Leicher-Duber et al, 1990). CDP-TM type is an autosomal dominant condition characterized by mesomelic limb shortening secondary to short tibiae with long proximal fibulae and short ulnae, and short metacarpals (Rittler et al, 1990). Savarirayan et al (2004) have reported the long-term follow-up of three cases of CDP-TM type, detailing its natural history.…”
Section: Unknown Aetiologymentioning
confidence: 99%
“…Five different types of chondrodysplasia punctata are currently distinguished: autosomal dominant (Conradi–Hünermann) (1,2), X‐linked dominant (Happle) (3), autosomal recessive (Rhizomelic dwarfism) (4), X‐linked recessive (5), and probably an autosomal dominant tibio‐metacarpal form (6). Table 1 summarizes the clinical findings in different types of chondrodysplasia punctata.…”
Section: What Syndrome Is This?mentioning
confidence: 99%